High levels of CD20 expression predict good prognosis in chronic lymphocytic leukemia - Fang, Cheng (Cancer Sci, 2013)
Heterogeneity of CD20 expression exists in chronic lymphocytic leukemia (CLL), therefore, we explored the prognostic significance of CD20 expression in Chinese patients with CLL. Multiparameter flow cytometry was used to detect the expression of CD20 in CD5(+) CD19(+) cells. In 172 CLL patients, the median expression percent of CD20 was 97.82% (range, 0–100), and the median mean fluorescence intensity (MFI) of CD20 in CLL cells was 731.45 (range, 0.00–9071.90). The percentage of CD20(+) cells in the patient group with mutated variable region of immunoglobulin genes (IGHV) was higher than in the non‐mutant IGHV group (mean, 92.1% vs 80.4%, P < 0.001). There were no differences in the MFI of CD20(+) cells in all prognostic factor groups. Representation of the data using a receiver operating characteristic plot reflected separation between the two IGHV groups, with an area under the curve of 0.661 (95% confidence interval, 0.569–0.753). At the cut‐off value of 60.3% for percentage of CD20, the sensitivity and specificity were 90.00% and 38.46%, respectively. Patients whose percentage of CD20 antigen was above 60.3% had longer treatment‐free survival (hazard ratio, 0.452; 95% confidence interval, 0.232–0.884, P = 0.020). Percentage and MFI of CD20 were the variables not associated with treatment‐free survival by multivariate Cox regression analysis (P < 0.05). High level of CD20 expression in de novo CLL appears to be associated with a good prognosis.